(untitled) (International Journal of Engineering and Computer Science, 2015)
Due to wide range of applications of cloud computing it has become very popular in current era of the computing. Many companies and academies has started migrating their data from their expensive servers to clouds. This work deals with providing the testing of software as a service via clouds. As known in prior: the testing is very critical and costly part of software development. So this paper we find the various directions or circumstances to provide software testing as a service. In this paper we also described different tools that used to test the software via cloud. By using TSAAS we minimize the cost of software testing. Different researchers used different methods to test the software, web applications, mobile applications via cloud computing . Keywords: Software